2012
DOI: 10.1007/s12094-012-0919-7
|View full text |Cite
|
Sign up to set email alerts
|

Sacral chordoma: management of a rare disease in a tertiary hospital

Abstract: In our experience, the best treatment is complete excision of the tumor with clear microscopic margins. When this is not possible, local recurrences increase and survival rate decreases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The mean operative time in most previous reports were 5–10 h, and the mean blood losses were 3900–5200 ml. [ 17 20 29 33 34 ] Only sufficient experience with navigation can increase the safety of surgery, otherwise the operation time and related risk may be elevated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean operative time in most previous reports were 5–10 h, and the mean blood losses were 3900–5200 ml. [ 17 20 29 33 34 ] Only sufficient experience with navigation can increase the safety of surgery, otherwise the operation time and related risk may be elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Housari et al . [ 34 ] reported 13 patients with a mean follow-up of 4.5 years and all nine recurrences occurred within the first 2 years postoperatively. Although our follow-up was relatively short compared with previous reports, satisfactory resection margin and good local control were achieved during a period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Chordoma is an uncommon malignant bone tumor of the axial skeleton; it is assumed to originate from residual embryonic notochord and accounts for approximately 1%‐4% of all skeletal tumors . Chordomas are chemoresistant and relatively radioresistant . Unfortunately, more than 40% of patients present with local recurrence, and metastases occur in 40%‐60% of patients during follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…1 Chordomas are chemoresistant and relatively radioresistant. [2][3][4] Unfortunately, more than 40% of patients present with local recurrence, and metastases occur in 40%-60% of patients during follow-up. There is currently no standard medical therapy for chordoma.…”
mentioning
confidence: 99%
“…Therefore, most of the local recurrences were associated with bone. Previous reports [7,17,18] have also shown most recurrences were located around the sacrum and other sites including the gluteus maximus and ischioanal fossa. Xie et al [16] assessed 30 patients with recurrent sacral chordomas and found that most recurrent tumors were located in sacrum (20 patients) and that some were located in the gluteus maximus (6 patients).…”
Section: Discussionmentioning
confidence: 88%